Portuguese real-world experience with ibrutinib for the treatment of relapsed/refractory mantle cell lymphoma - Fernandes, Catarina; Costa e Sousa, Rita; Santos, Pedro; Almeida, Cátia; Roque, Adriana; Pinto, Ana Luísa; Monteiro, Joaquim; Neves, Anabela; Ramos, Maria João; Coutinho, Rita; Mousinho, Filipa; Fernandes, Mariana Leal; et al. (Frontiers in Hematology, 2025)
BackgroundMantle cell lymphoma is usually characterized by an aggressive and recurrent course. Clinical trials and real-world series have demonstrated clinical benefits with the use of ibrutinib as a second-line treatment, compared to later relapses.ObjectiveTo evaluate the Portuguese experience with the use of ibrutinib in patients with relapsed or refractory mantle cell lymphoma since its approval in the country.MethodsA multicenter retrospective cohort of patients with mantle cell lymphoma who received ibrutinib between 2015 and 2020 was studied.ResultsNinety-five patients treated at 11 hospitals were included. At the ibrutinib starting date, 51% of patients had high-risk simplified mantle cell lymphoma international prognostic index, 9% had central nervous system involvement, and 21% had Eastern Cooperative Oncology Group performance status ≥2. The median treatment duration was 10 (<1-75) months. The overall response rate was 66%, including 36% with complete responses. After 18 months of follow-up, seventy-two patients (76%) had discontinued ibrutinib, mainly due to progressive disease (61%) and toxicity (21%). At the last follow-up, 24% of patients were still on ibrutinib, and 60% had died, mostly (65%) due to lymphoma progression.ConclusionsIn this real-world series, the safety of ibrutinib is similar to the results described in clinical trials. However, new strategies are needed for the treatment of acquired resistance to ibrutinib.